Algorithm for calculation of cephalometric soft tissue facial traits - Azam Rana, Mohammad; Setan, Halim; Majid, Zulkepli; Chong, Albert K. (2007)
Treatment planning of facial attractiveness is difficult. One of the primary goals of orthodontic treatment is to attain and preserve optimal facial attractiveness. For this, it is important that the orthodontist conduct a thorough facial examination so that the orthodontic correction will not adversely affect the normal facial traits. By knowing the soft tissue traits and the normal range, a treatment plan can be designed to normalize the facial traits for a given individual. This paper presents development of a new soft tissue analysis algorithm, which will be used as an analysis tool in Computer Assisted Craniofacial Surgery Planner – a surgery planning system under development. This analysis tool may be used by surgeons as an aid in diagnosis and treatment planning. This research uses 19 landmarks to calculate 18 facial traits such as facial profile angle, nasal projection, nasolabial angle, lower face height, maxillary sulcus contour, interlabial gap, throat length etc. The proposed algorithm allows picking the required landmarks interactively and then allows adjustment in the position of each landmark precisely. The source data used to get 3D digital models of human soft tissues include CT data and 3D laser scanner data. Up to now Malaysia does not have any source for normal trait values of human face. This algorithm can be used to calculate facial traits for building a nationwide database that can be used to compare normal traits with abnormal ones and then plan the surgery procedures. The system is the result of collaboration between a university, an industrial research organization and a research hospital. In this paper, components of the cephalometric analysis tool are detailed. Issues related to future research and plans for expanding the current system are discussed.